Factors influencing students’ intention to use internet for academic purposes - Bidin, Zainol; Mohd Shamsudin, Faridahwati; Md Hashim, Mohd Farid Asraf; Sharif, Zakiyah (Social Science Electronic Publishing, Inc, 2011)
This study aimed to investigate the factors influencing students’ intention to use the Internet for academic purposes amongst 204 final year business students in public universities in Malaysia.This study integrated theory of planned behavior (TPB) and theory of acceptance model (TAM) as the base model toward that purpose.The research model employs the variables from both theories namely attitudes, subjective norms, perceived behavioral control, perceived usefulness, perceived ease of use, intention, and behavior.A multiple regression analysis provides empirical support for the applicability of integration of TPB and TAM in predicting students’ intention to use the Internet for academic purposes.Results of the study show that attitudes, perceived behavioral control, and perceived usefulness are statistically significant in influencing intention to use the Internet for academic purposes.Based on the results, it can be concluded that students’ intention to use the Internet for academic purposes could be predicted from their attitudes, perceived behavioral control, and perceived usefulness at 49% level.In view of the results, several implications and recommendations are discussed.